Translating Timing into an Architecture: The Synergy of COTSon and HLS (Domain Expertise—Designing a Computer Architecture via HLS). (3rd November 2019) - Giorgi, Roberto; Khalili, Farnam; Procaccini, Marco
Abstract : Translating a system requirement into a low-level representation (e.g., register transfer level or RTL) is the typical goal of the design of FPGA-based systems. However, the Design Space Exploration (DSE) needed to identify the final architecture may be time consuming, even when using high-level synthesis (HLS) tools. In this article, we illustrate our hybrid methodology, which uses a frontend for HLS so that the DSE is performed more rapidly by using a higher level abstraction, but without losing accuracy, thanks to the HP-Labs COTSon simulation infrastructure in combination with our DSE tools (MYDSE tools). In particular, this proposed methodology proved useful to achieve an appropriate design of a whole system in a shorter time than trying to design everything directly in HLS. Our motivating problem was to deploy a novel execution model called data-flow threads (DF-Threads) running on yet-to-be-designed hardware. For that goal, directly using the HLS was too premature in the design cycle. Therefore, a key point of our methodology consists in defining the first prototype in our simulation framework and gradually migrating the design into the Xilinx HLS after validating the key performance metrics of our novel system in the simulator. To explain this workflow, we first use a simple driving example consisting in the modelling of a two-way associative cache. Then, we explain how we generalized this methodology and describe the types of results that we were able to analyze in the AXIOM project, which helped us reduce the development time from months/weeks to days/hours.